Green machining of aluminum pipes: an integrated approach for eco-efficiency and life cycle assessment in manufacturing systems - Firmino, Alessandro Silveira; Akim, Erica Kushihara; Oliveira, José Augusto de [UNESP]; Silva, Diogo Aparecido Lopes (Springer Nature, 2022)
Manufacturing processes are performed to convert raw materials into products. To do this, natural resources are consumed and emissions are generated with potential for adverse environmental impacts. To obtain a productive system with fewer negative impacts on the environment, green manufacturing (GM) was used in this work, in which the environmental performance of an aluminum pipe machining was studied through the application of an integrated approach based on life cycle assessment (LCA) and eco-efficiency indicators. The proposed framework uses the unit process life cycle inventory (UPLCI) methodology followed by the eco-efficiency assessment to support decision-making in four levels: “win–win,” “lose-lose,” and two trade-offs reference-situations. The results contributed to the identification of the electricity and cutting fluid consumptions as the main life cycle hotspots to be minimized. Through a sensitivity analysis, future manufacturing scenarios were proposed to reduce the life cycle impacts based on eco-efficiency assessments. A “win–win” situation was found for the scenario that duplicates the number of parts manufactured at each production cycle, increasing from three to six machined parts per cycle, and reducing by 25% the volume of raw material to be machined. All of these enabled reductions in the life cycle impacts by up to 16.47% and has increased eco-efficiency by up to 23.55%. Finally, the integrated approach for LCA and eco-efficiency assessment can be used as an easy way to advance sustainability scenarios in manufacturing systems.
Keywords: Eco-efficiency of processes; LCA of machines; Manufacturing system analysis; Sustainable manufacturing; Sustainable production